Good and bad sugars: Australian adults' perspectives on sugar in their diet. Issue 5 (20th October 2021) - Gupta, Adyya; Braunack-Mayer, Annette; Smithers, Lisa; Harford, Jane; Coveney, John
ABSTRACT: This study analyses the relationship between food choices and morality by exploring how Australian adults conceptualise and negotiate their sugar intake. Fifteen in-depth, semi-structured interviews were conducted with English speaking adults residing in South Australia. Participants were purposively sampled from a national survey based on their sugar consumption levels, age and gender. The data were analysed using thematic analysis. Participants initially defined sugars as good or bad based on source, colour, texture, taste and impact of sugar on health. On being provided with evidence on amounts of sugar present in commonly consumed foods and drinks, participants redefined their perceptions to consider all sugars as bad sugars. This created moral challenges for the participants leading to two types of justifications for their own sugar consumption. One group of justifications drew on socially evaluative statements that participants used to present themselves as morally virtuous. Here sugar was considered as an essential source of energy and part of a balanced diet; limited to infrequent occasions such as celebrations, social gatherings and cultural practices; and as a cultural obligation. The second group of justifications located the source of morality within the individual and presented sugar intake as important for emotional and psychological wellbeing, and also as something that could be controlled by taking responsibility. There were no differences in discourses between low and high sugar consumers. This study provides new insights on how Australians conceptualise sugar in diet and make consumption decisions, which are important for influencing sugar consumption at a societal level.